Implementasi Pengalaman Panca Indra pada Interior Restoran Shao Kao Surabaya - Melinda Chrysania Legawaputri; Sriti Mayang Sari; Celine Junica Pradjonggo (Intra, 2018)
Human’s ability to perceive a space is influenced by the experience of the five senses. However, this often considered unimportant and less noticed by the restaurant management and designer. In fact, customer’s experience is a very important factor in maintaining the interest in a restaurant. The purpose of this research is to understand the importance of sensory experience and how it is implemented on the interior, especially in Shao Kao Restaurant in Surabaya. The research method used is qualitative descriptive with the basic reference of the theory according to Deplasez and Andrea in the book Constructing Architecture, also Malnar and Vodvarka in the Sensory Design book about five senses and interior elements perceived by the five senses. Based on the analysist that has been done, it can be concluded that the human senses are very important in perceiving and experiencing a space. Each customer of Shao Kao Restaurant has a different experience on restaurant’s interior. The experience that involves the five senses is obtained through the application of interior elements in Shao Kao restaurant’s interior, which are lighting, color, Chinese-themed paintings as decorative elements, smells, sounds or noise, music, and room temperature, which then generates an atmosphere experienced by each visitor.